Procter & Gamble : oral care in China. - Ivina. (2008)
The report will begin by looking at the current situation of the oral care industry in China followed by a detailed analysis of the marketing strategies that P&G embarked on for its oral care brands in China. The P&G marketing strategies will then be compared with its closest competitors in the toothpaste and toothbrush markets. These competitors include international players, Colgate and Unilevel, and local players Aoqili, Liangmianzhen and Wuhan Jinchen.